Bilateral Craniofacial Cleft (Tessier Type 4): Case Report and Oculoplastic Reconstruction. (October 2021) - Chahal, Harinder S.; Viruni, Narine; Patel, Rooshil; Glover, A. Tyrone
Bilateral Tessier type 4 craniofacial clefts are extremely rare and disfiguring malformations with vision-threatening ramifications. To date, there is no consensus in the literature with respect to the ideal surgical technique and management of these patients. Emergent eyelid reconstruction and additional procedures may be required to protect the cornea and avoid further ophthalmic and surgical complications. We present our experience and challenges of managing a case of bilateral Tessier type 4 clefting with an emphasis on oculoplastic considerations.